The protective impact of adapted trimebutine maleate-loaded nanostructured lipid carriers for alleviating the severity of acute colitis - Amira Motawea; Walaa Ebrahim Abd El Hady; Ghada Ahmed El-Emam (Taylor & Francis Group, 2022)
Nanoparticles for colon-drug delivery were designed and evaluated to solve many discrepancy issues such as high adverse effects of released drugs, insufficient drug amount at diseased areas, and unintentionally premature drug release to noninflamed GIT regions. Herein, the goal of this work was to convert trimebutine maleate (TMB) into nanostructured lipid carriers (NLC) in order to improve its protective effects in ulcerative colitis. NLC of TMB was prepared by the hot homogenization followed by ultra-sonication method. A full 42-factorial design was used to estimate the produced TMB-NLC. The study design included the exploration of the impact of two independent variables namely lipid mix amount and ratio (glyceryl mono stearate and capryol 90), surfactant concentration (0.5, 1, 1.5, and 2%), on the particle size, polydispersity index, and the entrapment efficiency (EE%). The protective activity of F9 was examined through macroscopical scores, histopathological changes, immunohistochemical localization of tumor necrosis factor-α (TNF-α) and examination of oxidative stress such as reduced glutathione (GSH), superoxide dismutase (SOD), and malondialdehyde (MDA) against acetic acid-induced colitis in rats. Consistent with our expectations, the orally administered optimized formula (F9) alleviated the severity of colitis in acetic acid-induced rat model of colitis likely owing to the controlled release compared to free TMB. We aimed to develop TMB-loaded NLC for the treatment of acute colitis with the goal of providing a superior drug safety profile over long-term remission and maintenance therapy.